A Pre-Post Study on Efficacy of Celecoxib and Ibuprofen for Acute Low Back Pain among Orthopaedic Patients at Security Forces Hospital, Makkah, Saudi Arabia - H. Alzahrani, Khalid H. Alzahrani; A. Imam, Ethar; Ibrahim, Mohamed Izham Mohamed (Journal of Pharmacy Practice and Community Medicine)
Background: The safety and efficacy of Celecoxib and Ibuprofen have not been adequately examined among orthopaedic Arab patients. This prospective study was carried out to compare the benefits of Celecoxib and Ibuprofen with reference to factors affecting patients with acute low back pain. Methods: Pre-post study was carried out at orthopaedic Out Patient Department at Security Forces Hospital, Makkah, and KSA. One hundred and nine patients were randomly selected and assigned randomly to two treatment groups: Celecoxib 400 mg, and Ibuprofen 100 mg. Pain was assessed using the World Health Organization pain scale. The decrease in pain score was calculated using a standardized system and was recorded on Day 5 and Day 10 of the patients follow up visits. Paired sample t-test, Mann-Whitney test and Chi-Square test were used at alpha level 0.05. Results: All the patients were Saudi nationals. Patients’ age for Celecoxib group ranged from 20 – 59 years (34.2 + 10.9), while for Ibuprofen group ranged between 22 – 57 years (31.3 + 7.3). There were significant reductions in pain by both Celecoxib and Ibuprofen at the second follow-up visit, for all patients during walking, twisting, and while sitting in chair (p < 0.05). Celecoxib (400 mg) was superior to Ibuprofen (100 mg) in reducing acute low back pain of the study population (p < 0.05). The pain scores of patients receiving celecoxib and ibuprofen were significantly improved from Day 5 to Day 10. Conclusion: Celecoxib was more effective than Ibuprofen in reducing acute low back pain among the study population.
Keywords: Acute Low Back Pain; Evaluation; Management; Non-Steroidal Anti-Inflammatory Drugs; Orthopaedic Patients; Outpatient; Pain Scale